2018
DOI: 10.2217/imt-2018-0168
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Outcomes Associated with Treatment Sequences In Patients With BRAF -Mutant Advanced Melanoma

Abstract: Aim: The cost–effectiveness of treatment sequences in BRAF-mutant advanced melanoma. Materials & methods: A discrete event simulation model was developed to estimate total costs and health outcomes over a patient's lifetime (30 years). Efficacy was based on the CheckMate 067/069 trials and a matching-adjusted-indirect comparison between immuno-oncology and targeted therapies. Safety, cost (in US dollars; US third-party payer perspective) and health-related quality-of-life inputs were based on published lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 44 publications
(62 reference statements)
3
21
1
1
Order By: Relevance
“…Although the survival rate was better with subsequent nivolumab plus ipilimumab, a higher proportion of patients received subsequent anti-PD-1 monotherapy than nivolumab plus ipilimumab (24 vs 13%), which may have been due to the better safety profile with anti-PD-1 monotherapy. A sequencing model incorporating data from the CheckMate 067 and 069 and COMBI-v and COMBI-d studies also showed that total life-years were higher in patients who initiated first-line nivolumab plus ipilimumab followed by subsequent BRAF plus MEK inhibitors (8.4 years) compared with first-line anti-PD-1 therapies followed by subsequent BRAF plus MEK inhibitors (6.9 years) or first-line BRAF plus MEK inhibitors followed by subsequent anti-PD-1 therapy (3.2 years) [21]. Although this study did not include patients treated with first-line BRAF plus MEK inhibitors followed by nivolumab plus ipilimumab due to lack of data availability on this sequence, the results showed that treatment with first-line nivolumab plus ipilimumab followed by subsequent BRAF plus MEK inhibitors yielded the most benefit and was cost-effective [21].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the survival rate was better with subsequent nivolumab plus ipilimumab, a higher proportion of patients received subsequent anti-PD-1 monotherapy than nivolumab plus ipilimumab (24 vs 13%), which may have been due to the better safety profile with anti-PD-1 monotherapy. A sequencing model incorporating data from the CheckMate 067 and 069 and COMBI-v and COMBI-d studies also showed that total life-years were higher in patients who initiated first-line nivolumab plus ipilimumab followed by subsequent BRAF plus MEK inhibitors (8.4 years) compared with first-line anti-PD-1 therapies followed by subsequent BRAF plus MEK inhibitors (6.9 years) or first-line BRAF plus MEK inhibitors followed by subsequent anti-PD-1 therapy (3.2 years) [21]. Although this study did not include patients treated with first-line BRAF plus MEK inhibitors followed by nivolumab plus ipilimumab due to lack of data availability on this sequence, the results showed that treatment with first-line nivolumab plus ipilimumab followed by subsequent BRAF plus MEK inhibitors yielded the most benefit and was cost-effective [21].…”
Section: Discussionmentioning
confidence: 92%
“…A sequencing model incorporating data from the CheckMate 067 and 069 and COMBI-v and COMBI-d studies also showed that total life-years were higher in patients who initiated first-line nivolumab plus ipilimumab followed by subsequent BRAF plus MEK inhibitors (8.4 years) compared with first-line anti-PD-1 therapies followed by subsequent BRAF plus MEK inhibitors (6.9 years) or first-line BRAF plus MEK inhibitors followed by subsequent anti-PD-1 therapy (3.2 years) [21]. Although this study did not include patients treated with first-line BRAF plus MEK inhibitors followed by nivolumab plus ipilimumab due to lack of data availability on this sequence, the results showed that treatment with first-line nivolumab plus ipilimumab followed by subsequent BRAF plus MEK inhibitors yielded the most benefit and was cost-effective [21]. In contrast to the results of the current study, a recent retrospective study showed that survival was similar in patients receiving the combination of nivolumab plus ipilimumab or anti-PD-1 monotherapies following failure of targeted therapy in those with poor prognostic factors [22].…”
Section: Discussionmentioning
confidence: 92%
“…[2][3][4] Combination therapy with nivolumab plus ipilimumab has also had clinical efficacy in patients with metastatic melanoma and untreated brain metastases. 5,6 Some patients who have received nivolumab plus ipilimumab have also discontinued therapy without subsequent systemic treatment for melanoma 4,[7][8][9] ; this is one aspect of the value of combination nivolumab plus ipilimumab treatment. In this article, we provide an update of survival outcomes from the CheckMate 067 trial with a minimum of 5 years of follow-up as well as an assessment of the longterm benefit of combination nivolumab plus ipilimumab treatment with respect to outcomes in patients who have not received subsequent systemic treatment for melanoma and with respect to health-related quality of life.…”
mentioning
confidence: 99%
“…However, responses with combination immunotherapy are viewed as more durable [5,18] and can frequently be sustained even with treatment cessation. In this regard, our recent work has shown that initiating first-line treatment with immunotherapy (anti-PD-1 + anti-CTLA-4 or anti-PD-1) yields a longer survival benefit compared with combination BRAF + MEK inhibitors, driven by a long treatment-free interval [27]. Based on this durability of response, many providers favor immunotherapy for patients with BRAF-mutant melanoma; however, others may have safety concerns, particularly for those with comorbidities.…”
Section: Discussionmentioning
confidence: 99%